A Security Authentication Protocol for Trusted Domains in an Autonomous Decentralized System - Ruikang Zhou; Yingxu Lai; Zenghui Liu; Yinong Chen; Xiangzhen Yao; Jiezhong Gong (International Journal of Distributed Sensor Networks)
Software Defined Network (SDN) architecture has been widely used in various application domains. Aiming at the authentication and security issues of SDN architecture in autonomous decentralized system (ADS) applications, securing the mutual trust among the autonomous controllers, we combine trusted technology and SDN architecture, and we introduce an authentication protocol based on SDN architecture without any trusted third party between trusted domains in autonomous systems. By applying BAN predicate logic and AVISPA security analysis tool of network interaction protocol, we can guarantee protocol security and provide complete safety tests. Our work fills the gap of mutual trust between different trusted domains and provides security foundation for interaction between different trusted domains.